2011
DOI: 10.1179/1362171810y.0000000030
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation phenomena of magnesium from droplet at welding wire tip in pulsed MIG arc welding of aluminium alloys

Abstract: A lot of welding fumes are generated due to the evaporation of magnesium during welding aluminium alloys using Al-Mg welding wires. Fume formation is mainly evaluated by two methods. An average formation rate can be calculated by collecting the fumes formed during a constant welding period. The other one is carried out by observing the droplet with a high speed video. However, these two methods become invalid in quantitatively evaluating the evaporation rate of magnesium in peak or background period during pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…As shown by numerical estimates [27], metal inside the drop is involved into eddy motion, caused by Marangoni effect and influence of electromagnetic forces. Intensive stirring of drop metal is also confirmed by experimental studies [28]. As a result, convective mechanism of heat transfer in drop metal prevails over the heat conductivity process.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…As shown by numerical estimates [27], metal inside the drop is involved into eddy motion, caused by Marangoni effect and influence of electromagnetic forces. Intensive stirring of drop metal is also confirmed by experimental studies [28]. As a result, convective mechanism of heat transfer in drop metal prevails over the heat conductivity process.…”
supporting
confidence: 56%
“…Studying the dynamics of neck thinning and breaking at drop detachment, in particular formation of satellite drops, is of considerable interest, as well as physical processes running in the already detached drop [35]. In addition, hydrodynamic processes in the drop metal lead to emergence of convective diffusion of alloying elements [28]. Transport of alloying elements with a low boiling temperature, from fusion boundary to drop free surface, increases their evaporation intensity.…”
mentioning
confidence: 99%
“…One of the important points of arc welding of aluminium alloys is the danger of burnout alloying elements of the wire and the base metal [15]. Thus, during pulsed MIG welding in argon at an increased current, the temperature of the electrode metal droplets grows (up to the temperatures of 2100−2600 K), which leads to an intensive burnout of magnesium in them (content of magnesium is 2−3 times decreased and more) [16]. Due to burnout magnesium, in the electrode metal droplets pores can be formed, which in the process of mass transfer get into the welding pool and can result in porosity of the welds.…”
Section: Scientific and Technicalmentioning
confidence: 99%
“…Since the boiling point of magnesium is 1090 • C, the vaporization of magnesium will occur. In the study of Wang [12], the volume temperature of the aluminum alloy filler wire was measured when the peak current was 335 A during GMA welding, and it was about 1700-1730 K (1427-1457 • C), which caused the magnesium to vaporize. Studies on the deterioration of the mechanical properties caused by the vaporization of magnesium when welding aluminum alloys have been reported in the gas tungsten arc (GTA) welding process and the laser welding process, but studies of the GMA welding process have not been reported [13][14][15].…”
Section: Introductionmentioning
confidence: 99%